(untitled) (Global Journal of Science Frontier Research, 2015)
The waterfront development as a global phenomenon has been disclosed by studies at different perspectives. This study inquires the interrelationship between development units and development bodies and therefore stresses that development units with diverse attributes should be developed by different development bodies since the failure of adequate match between the former and the latter results in the underdeveloped development functions and values. This study presents the interrelationship between development units and development bodies through a waterfront development project in Taiwan. The seemingly simple development principle that is overlooked in many waterfront development projects has caused the procrastination or even the failure of development projects.